2007
DOI: 10.1016/j.ajog.2006.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance with hormone replacement therapy: associations with markers of inflammation and adiposity

Abstract: Objective-To determine if insulin resistance associated with combination hormone replacement therapy (HRT) is mediated by changes in serum markers of inflammation or in serum adipocyte hormones.Study design-Forty-five postmenopausal women, aged 55 ± 7 years, were examined from a randomized, double-blind placebo-controlled trial evaluating the effect of HRT on insulin-stimulated glucose disposal and body composition. Volunteers were randomized to conjugated estrogens 0.625 mg plus medroxyprogesterone acetate 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…In the present study, neither treatment affected the BMI (Table 1). In other studies, PE treatment has been combined with progesterone, resulting in either no change [20,27] or decrease [28] in plasma adiponectin concentrations; but the use of progesterone prevents a reliable comparison with our results.…”
Section: Discussioncontrasting
confidence: 74%
“…In the present study, neither treatment affected the BMI (Table 1). In other studies, PE treatment has been combined with progesterone, resulting in either no change [20,27] or decrease [28] in plasma adiponectin concentrations; but the use of progesterone prevents a reliable comparison with our results.…”
Section: Discussioncontrasting
confidence: 74%
“…The expression of estrogen-binding receptors in the microenvironment has been positively correlated to levels of inflammatory cytokines IL-1␤, TNF-␣, and IL-6 [26]. Furthermore, estrogen has been found to induce pro-inflammatory cytokines IL-1␤, TNF-␣, and C-reactive protein and to generate reactive oxygen species and nitrogen species [27,28]. In contrast, estrogen in combination with progesterone has been found to decrease IL-1␤-stimulated vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 [29], important in inflammatory reactions.…”
Section: Introductionmentioning
confidence: 96%
“…It has been demonstrated that hormone replacement therapy decreases insulin sensitivity (9). Moreover, it has been argued that insulin-sensitive obesity is mainly a phenotype seen in premenopausal women, who become insulin resistant after menopause.…”
Section: Clinical and Metabolic Characteristics Of Is And Ir Obesitymentioning
confidence: 99%